1986
DOI: 10.1088/0022-3727/19/10/013
|View full text |Cite
|
Sign up to set email alerts
|

Negative ion drift velocities in mixtures of methane and sulphur hexafluoride

Abstract: The velocities of negative ions drifting in mixtures of methane and sulphur hexafluoride have been measured. Measurements were made as a function of gas composition, reduced electric field strength between 3 and 185 Td, and total gas pressure in the range 100-600 Torr at 300K. The data indicate that SF6- (SF6) ions are the dominant ion in all of the gas mixtures studied. Extrapolation of the data using Blanc's Law was used to determine the velocity of sulphur hexafluoride ions drifting in pure methane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1987
1987
2011
2011

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…In calculating the ion drift velocities of the negative ions we have used the data of Cornell and Littlewood (1986), who suggested that the SF;(SF6) ion is dominant at these pressures. For the positive ions we have used the results of Fleming and Rees (1969).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In calculating the ion drift velocities of the negative ions we have used the data of Cornell and Littlewood (1986), who suggested that the SF;(SF6) ion is dominant at these pressures. For the positive ions we have used the results of Fleming and Rees (1969).…”
Section: Resultsmentioning
confidence: 99%
“…The drift velocity of negative ions in mixtures of methane and sulphur hexafluoride have been measured by Cornell and Littlewood (1986). Those for the positive ions in the pure gases can be calculated from the Langevin polarisation limit of the reduced zero field mobility…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in some cases such as complex mixture analysis, improved selectivity and resolution is required. Three methods are commonly used to increase the selectivity of drift tube IM separations: (1) the use of higher electric fields and pressures, combined with longer drift tubes, has been used to achieve resolutions up to ≈200 [7][8][9][10][11][12], (2) the use of shift reagents [13][14][15][16][17], defined as chemicals which complex or react selectively with an analyte to form a gas-phase ion of decreased mobility and increased drift time, or (3) changes to the drift gas composition or temperature [18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of drift gas mixtures on ion mobility has been studied using atomic ions [19,[33][34][35], but there have been few reports of the use of binary drift gas mixtures in the analysis of molecular species to enhance ion mobility separations. The mobilities of SF 6 clusters in mixtures of SF 6 and methane have been reported using atmospheric pressure IM [19] and a 10% methane in argon drift gas mixture has been used to study the mobilities of low molecular weight aromatic compounds at atmospheric pressure using IM-MS [29].…”
Section: Introductionmentioning
confidence: 99%